-0.33-m=-0.11m+0.037-0.33m

Simple and best practice solution for -0.33-m=-0.11m+0.037-0.33m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.33-m=-0.11m+0.037-0.33m equation:


Simplifying
-0.33 + -1m = -0.11m + 0.037 + -0.33m

Reorder the terms:
-0.33 + -1m = 0.037 + -0.11m + -0.33m

Combine like terms: -0.11m + -0.33m = -0.44m
-0.33 + -1m = 0.037 + -0.44m

Solving
-0.33 + -1m = 0.037 + -0.44m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '0.44m' to each side of the equation.
-0.33 + -1m + 0.44m = 0.037 + -0.44m + 0.44m

Combine like terms: -1m + 0.44m = -0.56m
-0.33 + -0.56m = 0.037 + -0.44m + 0.44m

Combine like terms: -0.44m + 0.44m = 0.00
-0.33 + -0.56m = 0.037 + 0.00
-0.33 + -0.56m = 0.037

Add '0.33' to each side of the equation.
-0.33 + 0.33 + -0.56m = 0.037 + 0.33

Combine like terms: -0.33 + 0.33 = 0.00
0.00 + -0.56m = 0.037 + 0.33
-0.56m = 0.037 + 0.33

Combine like terms: 0.037 + 0.33 = 0.367
-0.56m = 0.367

Divide each side by '-0.56'.
m = -0.6553571429

Simplifying
m = -0.6553571429

See similar equations:

| -40=(x-10) | | 10-4x=30-44x | | -2(-2)-4(-2)= | | 323=-1+6(8a+6) | | 84-2x=98-3x | | -2x-2-4(-2)= | | 2-7(m-8)=114 | | Y=g(x-2) | | 1/9×=4 | | (X+3)4=y | | 9a^4x^5/4x/3a/2x | | 3(4-5n)=-78 | | 0.25k=3(-0.75k+3) | | 2v=v+13 | | 2b=b+88 | | 0.1(x-3)=1.1-0.25 | | b+10+7b=10 | | Z(2z+6)=3+z | | 4t-54=3t-9 | | 2n+6=48-5n | | -7n+10n=-33 | | (2(x^(1/2)))^2 | | 5t-92=t | | 1+7x+3x=21 | | 4p-32=p+31 | | 3m+5n=7 | | y=4y-30 | | -1=x-6+5 | | 2m=n-4 | | 21=4v-7v | | 9b-22=7b-16 | | -2(1-6r)=-2+4r |

Equations solver categories